Two new species of the genus Nigrimacula Shi, Bian & Zhou, 2016 (Orthoptera: Tettigoniidae: Meconematinae) from China - Ren, Bingyu; Xu, Hao; Zhu, Qidi; Chang, Yanlin (Zootaxa, 2025)
This paper reports two new species of the genus Nigrimacula Shi, Bian & Zhou, 2016 from China, i.e. Nigrimacula laminoprotubera sp. nov. and Nigrimacula dentiprotubera sp. nov. In addition, we provide the morphological photographs. All type specimens are preserved in the Museum of Hebei University.